Emotional Intelligence and Knowledge Hiding Behaviors: The Mediating Role of Job Stress - Wang, Xiangming; Dong, Baobao (Frontiers in Psychology, 2022)
Emotion is fundamental to human experiences influencing our daily activities including cognition, communication, learning, and decision making, but the effect of emotion on knowledge management in firms receives a little attention, especially in the field of knowledge hiding behaviors. Drawing on the cognitive appraisal theory of stress and coping as a unique theoretical lens to explicate how knowledge hiding behaviors happen, this study investigates the mediating effect of job stress in the relationship between emotional intelligence and knowledge hiding behaviors. We conducted a field study with 193 full-time employees to test our hypotheses. Results supported the mediating effects of job stress in accounting for the relationship between emotional intelligence and knowledge hiding behaviors. Our study is among the first to examine how emotional intelligence predicts knowledge hiding behaviors. Our study contributes to the literatures on knowledge management and emotional intelligence.